2011
DOI: 10.1111/j.1442-200x.2011.03361.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and gender‐specific reference intervals for serum lipid levels (measured with an Advia 1650 analyzer) in school children

Abstract: Unlike children in other developing countries, Saudi children do not have lower serum cholesterol than their Western counterparts. These findings reflect changing dietary habits and increasing affluence in Saudi Arabia. These reference intervals may be used to aid in the early assessment of cardiovascular risk in Saudi pediatric populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Table 2 summarizes the 2.5 th and 97.5 th percentiles of the glucose levels in boys and girls of different age groups ranging from 6 to 16 years. Table 3 shows the reference intervals for lipids for Saudi boys and girls, which were established recently and published [10]. We have found that in boys and at stage II, there was a significant positive correlation between glucose and cholesterol (r = 0.306, p < 0.001 n = 109) as well as between glucose and LDL (r = 0.317, p < 0.001 n = 109).…”
Section: Resultsmentioning
confidence: 70%
“…Table 2 summarizes the 2.5 th and 97.5 th percentiles of the glucose levels in boys and girls of different age groups ranging from 6 to 16 years. Table 3 shows the reference intervals for lipids for Saudi boys and girls, which were established recently and published [10]. We have found that in boys and at stage II, there was a significant positive correlation between glucose and cholesterol (r = 0.306, p < 0.001 n = 109) as well as between glucose and LDL (r = 0.317, p < 0.001 n = 109).…”
Section: Resultsmentioning
confidence: 70%
“…In comparison to data from other studies,34 36 37 Chinese children showed lower levels of TG, TC and LDL. This may be explained by the difference of diet, lifestyle, economic development and environment in various ethnicities 32 38 39. TG, TC, HDL, LDL, ApoA1 and ApoB levels in children of Han ethnicity in our area are higher than those of children with the same age in Beijing area 40.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, the Sinton method was used by Manning et al while the Lahti method was preferred by Ridefelt et al [24][25]. There are also certain studies frequently using the standard statistical methods in the literature [26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 98%